Identification and characterisation of carnostatine (SAN9812), a potent and selective carnosinase (CN1) inhibitor with in vivo activity - Qiu, Jiedong; Hauske, Sibylle J.; Zhang, Shiqi; Albrecht, Thomas; Pastene, Diego O.; Peters, Verena; Kannt, Aimo; Yard, Benito A.; Krämer, Bernhard; Hammes, Hans-Peter; Rodriguez-Niño, Angelica (Amino acids, 2019)
Carnosinase 1 (CN1) has been postulated to be a susceptibility factor for developing diabetic nephropathy (DN). Although its major substrate, carnosine, is beneficial in rodent models of DN, translation of these findings to humans has been hampered by high CN1 activity in human serum resulting in rapid degradation of carnosine. To overcome this hurdle, we screened a protease-directed small-molecule library for inhibitors of human recombinant CN1. We identified SAN9812 as a potent and highly selective inhibitor of CN1 activity with a Ki of 11 nM. It also inhibited CN1 activity in human serum and serum of transgenic mice-overexpressing human CN1. Subcutaneous administration of 30 mg/kg SAN9812 led to a sustained reduction in circulating CN1 activity in human CN1 transgenic (TG) mice. Simultaneous administration of carnosine and SAN9812 increased carnosine levels in plasma and kidney by up to 100-fold compared to treatment-naïve CN1-overexpressing mice. To our knowledge, this is the first study reporting on a potent and selective CN1 inhibitor with in vivo activity. SAN9812, also called carnostatine, may be used to increase renal carnosine concentration as a potential therapeutic modality for renal diseases linked to glycoxidative conditions.
Published online: 20 June 2018
Gesehen am 09.10.2019